Cochlear implantation under local anaesthesia – Our experience and a validated patient satisfaction questionnaire. (4th May 2017) - Mistry, Sandeep G.; Carr, Simon; Martin, Jane; Strachan, David R.; Raine, Christopher H.; Fyrmpas, Georgios
Abstract : Objectives : Cochlear implantation (CI) under local anaesthetic (LA) has previously been shown to be a successful and safe option for a specific group of patients (e.g. elderly and significant co-morbidity). We aim to discuss our practice and obtain qualitative information about patient experience from our cohort of patients at the Yorkshire Auditory Implant Service (YAIS). Methods : Retrospective chart review to include demographics, co-morbidities and physiological parameters were recorded and used to calculate P-POSSUM (Portsmouth Physiological and Operative Severity Score for the enumeration of Mortality and Morbidity) scores. The Iowa Satisfaction with Anaesthesia Scale (ISAS) questionnaire was distributed to all patients who received CI under LA and subsequently analysed. Results : Seven patients received CI under LA at YAIS. This included five males and two females. The mean age was 79 years (range 26 –93). The mean P-POSSUM mortality and morbidity for this cohort was 2.4 and 34.9%, respectively. The average ISAS score was +1.72 (where range of −3 is completely dissatisfied and +3 is completely satisfied). Discussion : We discuss our cohort and show that patients receiving CI have a favourable experience when LA is used. CI under LA is a viable and safe option for more elderly patients and those who are deemed at high risk of morbidity or mortality associated with a general anaesthetic. Conclusions : The data regarding validated patient experience obtained from this study can be used to help counsel patients that may be offered CI under LA.